Kong Koan records (Microfilmed by the Genealogical Society, 1989)
Records of the Kong Koan, an office of the Chinese community in Indonesia during the Dutch administration. Includes records of assistance to the poor, immigration records, burial records in the Feng Shui Cemetery in Jakarta, donations, accounts, minutes of meetings, travel passes, court cases, and records of births, marriages, deaths, and divorces.